Pengaruh Kemampuan Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Bank Sumut Cabang Medan Sukaramai - Syahputri, Nur Mustika; Harahap, Muhammad Ikhsan (Universitas Labuhanbatu, 2022)
This study was conducted to determine the influence of the ability and discipline of work on employee performance at PT. Bank Sumut Branch Medan Sukaramai. The population in this study is all employees at PT. Bank Sumut Branch Medan Sukaramai totaling 78 employees. The research samples were taken using saturated sampling technique where the entire population is used as a sample. The study was conducted from January to February 2022. The study used quantitative data processed with SPSS. The data analysis technique used is multiple linear regression model. The results of this study showed that the ability and discipline of work positive and significant effect both partially and simultaneously on the performance of employees at PT. Bank Sumut Branch Medan Sukaramai. T test shows the ability to have t count of 4.833 and significant of 0.000, and work discipline has t count of 8.401 and significant of 0.000. F test shows the value of F calculated obtained at 47.359 and significant at 0.000. The most dominant variable affecting employee performance is the variable of work discipline and ability. Determination test results showed 54.6% of employee performance at PT. Bank Sumut Branch Medan Sukaramai can be explained and obtained from the ability and discipline of work while the rest of the other factors.Â